Start your own lawn care or landscaping business : your step-by-step guide to success - Linsenmann, Ciree ([Irvine, Calif.] : Entrepreneur Press, 2011)
'A start up guide with ideas and various suggestions on starting your own lawncare and landscaping business'--
Includes bibliographical references and index.
Keywords: Lawn care industry -- Management; Landscaping industry -- Management; Small business; New business enterprises